Penerapan Metode Seven Tools Terhadap Kualitas Snack Kentang pada Osha Snack - Bilqis Bilqis; Davina Naswa Nur Amallina; Marizka Yukabad; Femi Aldilla Permata; Nur Khansa Al Qodariah; Dessy Damayanthy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Product quality is described as the characteristics of a product that supports its ability to meet customer needs standards or manufacturer feasibility standards. This research was conducted on potato chip products at Osha Snack by analyzing the types of defects in potato chips and their causative factors. In this study, the method used is the seven tools method, namely fishbone diagram, pareto diagram, and flowchart diagram. In one month, 57 units of defective potato chips were obtained. The purpose of this study using the seven tools method is to find out the types of defects in potato chips and the factors that cause defects in the product to minimize the level of defects in the production period in the next period. Based on the data obtained, there are two types of defects in potato chips, including 35 units of product returns and 22 units of burnt chips and inappropriate potato cutting. On the application of quality chips.